A Comparative Study of Coal Quality: Insights from Actual and Proximate Analysis Models - Tomi Sofyan; Alwi Zenar Wilogo; Arif Yasin Saputra; Rahmat Irjantoko; Partama Misdiyanta; Obrin Trianda (CV FOUNDAE, 2025)
Coal quality plays a pivotal role in determining its efficiency and environmental impact when used as a fuel source. This study aims to conduct a comprehensive comparison of coal quality by employing two analytical approaches: Actual Analysis and Proximate Analysis. Actual Analysis evaluates the fundamental characteristics of coal, including carbon content, hydrogen, sulfur, and trace elements. In contrast, Proximate Analysis focuses on determining moisture content (TM), ash (ASH), total sulphur (TS), and calorific velocity (CV). By integrating the insights gained from both models. The difference in coal quality is caused by the following factors, coal cleaning, coal getting, drainage making, and human error. Difference between actual coal quality parameters and model coal quality in January – March 2024; moisture content (TM) (0.2 - 1.59 % ar), ash (ASH) (0.76-5.01 % adb), total sulphur (TS) (0.1-0.6 % adb), calorific velocity (CV) ar (4-145 kcal/kg). In contrast, Proximate Analysis focuses on determining moisture content, volatile matter, ash, and fixed carbon. By integrating the insights gained from both models, this paper elucidates the strengths and limitations of each method, highlighting their relevance in industrial applications and environmental considerations. The findings provide a nuanced understanding of coal quality, paving the way for more informed decisions in its utilization and management. This study emphasizes the importance of selecting the appropriate analytical method to achieve optimal performance and sustainability in coal utilization.